CLINICALLY ORIENTED TEACHING OF PHYSIOLOGY THROUGH CASE BASED LECTURING - Rehman, Rehana (Pakistan Journal of Physiology, 2014)
Background: Case based lecture is an interactive student centred approach that promotes active learning by interaction of students. These lectures generate knowledge, organise it in a meaningful sequential manner which helps to associate problem in the clinical case with disturbance in normal mechanisms. The present study was undertaken to analyse perception of students about case based lectures in teaching of Physiology. Methods: It was a cross sectional descriptive study carried out from January to December 2010 among second year medical students of Bahria University Medical & Dental College. Case based lectures were carried out on systems of gastrointestinal, renal, neuroscience, endocrine and reproductive Physiology. A self-reported questionnaire was designed to evaluate positive and negative responses of students on usefulness of these lectures. Frequencies of responses were analysed. Results: A total of 17 case based lectures were carried out in a batch of 100 students and the questionnaire was responded at a rate of 98%. Medical students; 67 (68%) were able to understand core content of subject and 64 (65%) recognised its structure and functional relationship. Case based lectures helped students; 69 (70%) to integrate knowledge of basic health sciences with pathological aspects, 63 (64%) to identify illness and 64 (65%) to understand disturbance in mechanism which gives rise to disease. Conclusion: Majority of medical students were able to understand core content of Physiology in context with structural and functional relationships and pathological aspects with identification of disease by case based lectures. Pak J Physiol 2014;10(1-2):15–7